PERANAN MASYARAKAT DALAM MENYIKAPI PRO KONTRA WACANA PENUNDAAN PEMILU 2024 - Tamimi, Ruslan (Bahasa Indonesia, 2022)
Election is a means of people's sovereignty to elect members of the People's Representative Council, members of the Regional Representatives Council, the President and Vice President, and to elect members of the Regional People's Representative Council, which are conducted directly, publicly, freely, confidentially, honestly and fairly. There is no provision regarding the postponement of the 2024 election, but further elections and follow-up elections could occur due to riots, natural disasters, security disturbances and other disturbances. The method used in this research is to use a descriptive qualitative writing method to describe the situation that will be observed in the field. Efforts that need to be made are confirmation from the government to provide clarity on the schedule and transparency regarding the election agenda itself. If indeed the discourse of postponement needs to be realized, then we must look in the mirror with the guidance of the Constitution, so that what is the basis of the constitution does not conflict in democratic life.